THE CLASS STRUGGLE ANALYSIS OF MANCHESTER CHARTISM MOVEMENT IN ELIZABETH GASKELL’S A TALE OF MANCHESTER LIFE - SUKMAWATI, MEILINA (LANTERN (Journal on English Language, Culture and Literature), 2015)
This thesis is an analysis of a novel entitled Mary Barton: A Tale of Manchester Life by Elizabeth Gaskell. Overall, Mary Barton: A Tale of Manchester Life tells about the lifeof working class in Manchester. The purpose of this thesis are to analyze the effects, triggers and the exposition of the class struggle of the Chartism Manchester Movement in Mary Barton: A Tale of Manchester Life . To achieve the aims, the intrinsic aspects such as plot, characters and settings are employed in the analysis of the intrinsic elements of this novel. The writer also uses a sociological approach that is Marxist theory to analyze the social aspects of the novel. Marxist theory that focuses on the concept of class struggle is applied in the discussion of extrinsic aspects of this novel. The research method used in this study is library research by browsing the internet and reading some books. The result of this study shows that the class struggle of the Chartism Manchester Movement is encouraged by inequality of capitalist system where the workers are exploited by the system. This study also concludes that the working class struggle that is done by the Chartism Manchester Movement constructs the new system of employment in Manchester that will create a good relationship between the masters and the workers.